Tumor Evasion from T Cell Surveillance. (15th November 2011) - Töpfer, Katrin; Kempe, Stefanie; Müller, Nadja; Schmitz, Marc; Bachmann, Michael; Cartellieri, Marc; Schackert, Gabriele; Temme, Achim
Abstract : An intact immune system is essential to prevent the development and progression of neoplastic cells in a process termed immune surveillance. During this process the innate and the adaptive immune systems closely cooperate and especially T cells play an important role to detect and eliminate tumor cells. Due to the mechanism of central tolerance the frequency of T cells displaying appropriate arranged tumor-peptide-specific-T-cell receptors is very low and their activation by professional antigen-presenting cells, such as dendritic cells, is frequently hampered by insufficient costimulation resulting in peripheral tolerance. In addition, inhibitory immune circuits can impair an efficient antitumoral response of reactive T cells. It also has been demonstrated that large tumor burden can promote a state of immunosuppression that in turn can facilitate neoplastic progression. Moreover, tumor cells, which mostly are genetically instable, can gain rescue mechanisms which further impair immune surveillance by T cells. Herein, we summarize the data on how tumor cells evade T-cell immune surveillance with the focus on solid tumors and describe approaches to improve anticancer capacity of T cells.